Effects of the timing of births on women's earnings: Evidence from a natural experiment - Arizo Karimi (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
This paper studies the causal effect of the timing of first birth on highly educated women's career outcomes using exogenous variation in first birth timing induced by the occurrence of pregnancy loss before first birth. Contrasting previous findings, my results suggest that a one-year delay has a significantly negative effect on both income and wages. The negative effects might partly be explained by child spacing; motherhood delay induces women to have the second child more closely spaced (but not fewer or more children altogether), and consequently to have a potentially longer consecutive parental leave, or more frequent transitions in and out of the labor market. The same findings hold true when I employ an individual-fixed effects estimator based on panel data, from which the results suggest a larger slope decline in the wage profile post birth for "late" mothers. The hypothesis that short birth intervals may be detrimental for career outcomes is then tested by analyzing the impact of spacing births, using miscarriages between the first and second births as an instrument for birth spacing. The results suggest that a longer birth spacing indeed has positive long-run effects on income and wage rates.
Keywords: J31; J13; 330; first-birth timing; child spacing; female wages; lifetime earnings